THE TYPES OF WOMEN LANGUAGE FEATURES FOUND IN THE FAULT IN OUR STARS MOVIE - Utami, Ni Made Verayanti; Diah Priska, Ni Putu; Puspita Candra, Komang Dian (Lingual Journal of Language and Culture, 2020)
This study entitled The Types of Women Language Features found in The Fault in Our Stars movie. The study aimed to find out the types of women language features used by the female main character. This study focused on Lakoff’s theory (1975) about women language features. This study applied qualitative and quantitative methods in revealing the data. The study used note taking as a technique to get a valid data in collecting the data. The findings showed that there were 9 out of 10 types of women language features are used by the female main character. The finding show that intensifiers became the dominant type of women language features that uttered in this movie because the female main character in this movie was a typical of feminine girl who is always try to tell the hearers about her emotion or feeling through a sentence.